Reactive Power Tracing Index LQP_LT for Voltage Unstable Load Bus Identification in Power Systems - Renuga Verayiah; Azah Mohamed; Syahirah Abd Halim (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Existing power systems are significantly susceptible to voltage instability problem since such systems are stressed with the huge power transfers across the grids. To guarantee power system stability during stressed conditions, it is important to first identify the voltage unstable load buses to determine appropriate locations for under voltage load shedding. In this study, a new method is proposed for determining weak load bus locations by using reactive power tracing to develop a novel reactive power tracing capable index, named as LQP_LT.  The reactive power tracing algorithm is integrated with the LQP_LT index formulation to generate priority ranking list of weak load buses. The LQP_LT index was tested on the 57 bus system and the resulting priority ranking list is found to have successfully determined the weak load buses for load shedding in the test system. Comparison with other stability indices revealed that the LQP_LT has better sensitivity and response towards determining the location of the weakest load bus for under voltage load shedding implementation.